IBM Cognos 10 report studio cookbook : over 100 recipes that will show you how to use IBM Cognos 10 Report Studio to build creative, stunning, and sophisticated reports /: over 100 recipes that will show you how to use IBM Cognos 10 Report Studio to build creative, stunning, and sophisticated reports. (2013) - Unknown
No abstract available